High Thermoelectric Performance in Polycrystalline SnSe Via Dual‐Doping with Ag/Na and Nanostructuring With Ag8SnSe6. Issue 2 (28th November 2018) - Luo, Yubo; Cai, Songting; Hua, Xia; Chen, Haijie; Liang, Qinghua; Du, Chengfeng; Zheng, Yun; Shen, Junhua; Xu, Jianwei; Wolverton, Chris; Dravid, Vinayak P.; Yan, Qingyu; et al.
Abstract: Single crystalline SnSe is one of the most intriguing new thermoelectric materials but the thermoelectric performance of polycrystalline SnSe seems to lag significantly compared to that of a single crystal. Here an effective strategy for enhancing the thermoelectric performance of p‐type polycrystalline SnSe by Ag/Na dual‐doping and Ag8 SnSe6 (STSe) nanoprecipitates is reported. The Ag/Na dual‐doping leads to a two orders of magnitude increase in carrier concentration and a convergence of valence bands (VBM1 and VBM5 ), which in turn results in sharp enhancement of electrical conductivities and high Seebeck coefficients in the Ag/Na dual‐doped samples. Additionally, the SnSe matrix becomes nanostructured with dispersed nanoprecipitates of the compound Ag8 SnSe6, which further strengthens the scattering of phonons. Specifically, ≈20% reduction in the already ultralow lattice thermal conductivity is realized for the Sn0.99 Na0.01 Se–STSe sample at 773 K compared to the thermal conductivity of pure SnSe. Consequently, a peak thermoelectric figure of merit ZT of 1.33 at 773 K with a high average ZT (ZTave ) value of 0.91 (423–823 K) is achieved for the Sn0.99 Na0.01 Se–STSe sample. Abstract : An effective strategy for enhancing the thermoelectric performance of p‐type polycrystalline SnSe is proposed by Ag/Na dual‐doping and argyrodite Ag8 SnSe6 nanostructuring. The dispersed Ag8 SnSe6 nanoprecipitates are in situ precipitated when the Ag solubility is exceeded. The nanoprecipitates cause a strong scattering of phonons and result in an effective decrease of the already very low thermal conductivity of SnSe.